Pengaruh Motivasi Kerja Islami dan Tunjangan Terhadap Kinerja Karyawan BPRS Amanah Ummah Selama WFH - Siti Ramadhani; Kholil Nawawi; Syarifah Gustiawati (Indonesian Journal of Islamic Economics and Business, 2021)
The aim of this study was to find out the effect of Islamic Work Motivation and Performance Allowance to Employee Performance in BPRS Amanah Ummah Leuwiliang Bogor while working from home during The Coronavirus Pandemic. The approach of this research was quantitative, which defines a relationship or a measurable effect, making predictions based on reality with the data collected from published reports. The data was collected from questionnaires that have been filled by related respondents which are employees of BPRS Amanah Ummah Leuwiliang Bogor with a sample of 33 respondents by using Slovin’s formula sampling techniques. The analysis method of this research is using statistical package for the science (SPSS) application version 25. The results showed that there is a significant effect of Islamic Work Motivation on Work Performance. And there is a significant effect of Performance Allowance on Work Performance. So the conclusion is the higher of Work Motivation and Performance Allowance to employees will increase employees' performance.